2010
DOI: 10.1111/j.1365-2265.2009.03596.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrocortisone dosage scheme on health‐related quality of life in patients with adrenal insufficiency

Abstract: SummaryContext Recent studies suggest that current glucocorticoid replacement therapies fail to completely restore well-being in patients with adrenal insufficiency (AI). Objective The objective of this study was to investigate healthrelated quality of life (QoL) in patients with AI depending on dose and frequency of daily intake of hydrocortisone (HC). Design and patients In a cross-sectional study, primary and secondary AI patients were contacted and asked to complete three validated self-assessment question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
114
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 27 publications
13
114
1
1
Order By: Relevance
“…This is consistent with previous observational studies comparing patients with primary AI and SAI to normative control groups (2,7,8,9). One reason for impaired subjective health may be that common replacement regimens are not able to mimic the physiological diurnal pattern of cortisol secretion (1).…”
Section: Sai Patients (Nz18)supporting
confidence: 80%
See 3 more Smart Citations
“…This is consistent with previous observational studies comparing patients with primary AI and SAI to normative control groups (2,7,8,9). One reason for impaired subjective health may be that common replacement regimens are not able to mimic the physiological diurnal pattern of cortisol secretion (1).…”
Section: Sai Patients (Nz18)supporting
confidence: 80%
“…15 vs 20 mg). This is complemented by results of previous cross-sectional studies, which indicated an association between higher HC doses and impaired subjective health status (7,9). Unfortunately, our study design does not allow to clearly differentiate the effects of HC dosage and replacement regimen (i.e.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The reason is likely to be multifactorial, with aetiology, previous treatments, severity of the hypopituitarism and inadequate replacement therapy as potential important influencing factors (4,5,6). Patients with primary and secondary adrenal insufficiency (AI) also have impaired QoL (7,8,9). In a recent survey including Higher GC doses are also associated with more severe impairments of subjective health status in patients with AI (7,8).…”
Section: Introductionmentioning
confidence: 99%